Searching for common bean genotypes resistant to Acanthoscelides obtectus, a primary pest species of stored beans - Cabral, Isabella Rubio [UNESP]; Baldin, Edson Luiz Lopes [UNESP]; Faria, Rodrigo Donizeti [UNESP]; Silva, Jamilly Pereira; Dos Santos, Thais Lohaine Braga [UNESP]; de Oliveira Takaku, Vinicius Seiji [UNESP]; da Silva Santana, Alisson; Lima, Ana Paula Santana [UNESP]; Canassa, Vinicius Fernandes [UNESP]; Do Prado Ribeiro, Leandro (FapUNIFESP (SciELO), 2024)
Resistant genotypes are a valuable tool in integrated pest management programs of insect pests of stored grains. Here, we screened 90 Brazilian common bean genotypes to select promising sources of resistance to Acanthoscelides obtectus. Thus, bean samples were infested with newly emerged insects, and the number of eggs, emerged insects, developmental time, and larval viability were assessed in a no-choice test. Genotypes IPR Garça, CHIR 13, IAC Harmonia, CHIR 20, IAC Boreal, and CHIP 312 showed low oviposition. Genotypes IPR Quero-Quero, BRS Notável, CHIC 61-Cariocão, BRS Ametista, IPR Uirapuru, IAC Imperador, Avaluna, CHP 04-241A-212-Guapo B. × Uirapuru, CHIB 06, SCS 206-Potência, CHC 01-175-1-Campeiro × IAC Tibatã, CHP 01-182-48-Uirapuru × Campeiro, UEM 266, CHC 04-233-2-Siriri × Horizonte, CHV 17-64, SCS 205-Riqueza, CHP 01-238-80-MN 13337, SM 1510-preto, BRS Radiante, CHIB 18, CHIR 14, CAV 17 EFM 008, CHIR 04, IPR Campos Gerais, CHV 05-268-02, LP 13-624-preto, Linhagem 110-IAC, CHP 01-182-12-Uirapuru × Campeiro, LP 13-84-carioca, BRS Esteio, CHV 17-635, CHB 15-518, Arcelina 1, IPR Tuiuiu, SCS 204-Predileto, TB-17-02, BRS Estilo, SM 0511-cavalo preto, Pérola, IPR Tangará, and CNFRj-15411 reduced oviposition, the number of emerged adults, and larval viability, suggesting antixenosis and/or antibiosis. Thus, these genotypes are promising sources of resistance factors and can be used in breeding programs to obtain lines of common beans resistant to A. obtectus.
Keywords: antibiosis; antixenosis; bean weevil; host plant resistance; Phaseolus vulgaris